EVALUASI PERESEPAN OBAT PASIEN RAWAT JALAN PUSKESMAS SUNGAI TABUK 1 KALIMANTAN SELATAN TERHADAP FORMULAIRUM KABUPATEN - Okta Muthia Sari; Rollah Muhammad Arasy Hasan; Pretty Wulan Sari; Henni Selvina (Jurnal Insan Farmasi Indonesia, 2020)
Drug formularies are a guide for health workers in choosing drugs rationally. One of the benefits of formularies is controlling quality and optimizing services for patients. The conformity of prescription drugs to formularies is important to improve the quality of service. The purpose of this study was to assess the conformity of prescription drugs at Sungai Tabuk 1 Primary Health Care against the Banjar District Formulary for the period 2019. This retrospective descriptive study was conducted in January to February 2020 at the outpatient of Sungai Tabuk 1 Primary Health, South Kalimantan. Prescribing drugs at the outpatient of the 16 therapy classes, there are 13 therapy classes 100% according to the Banjar Regency Formulary for the period 2019. Meanwhile, 3 classes of less than 100% conformity therapy include anti-infection, topical medicines for the skin, and vitamins and minerals. The mean percentage of prescription drugs at the outpatient of Sungai Tabuk 1 in accordance with the Banjar Regency Formulary was 99.15.